2010
DOI: 10.1007/s00268-009-0364-0
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcome in 215 Children and Adolescents with Papillary Thyroid Cancer Treated During 1940 Through 2008

Abstract: Survival from childhood PTC should be expected, but later death from nonthyroid malignancy is disconcerting. Seventy-three percent of those who died from nonthyroid malignancy had received postoperative therapeutic irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
274
2
17

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(308 citation statements)
references
References 70 publications
15
274
2
17
Order By: Relevance
“…However, importantly, despite having more advanced disease, children are less likely to ultimately die of the disease than adults [29,30]. Fortunately, even in the presence of metastatic disease, 30-yr survival rates are as high as 90-99% [25,31].Survival is favourable in children even in metastatic disease than adults, since pulmonary metastases can remain stable for extended periods [28,32].…”
Section: Clinical Features and Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…However, importantly, despite having more advanced disease, children are less likely to ultimately die of the disease than adults [29,30]. Fortunately, even in the presence of metastatic disease, 30-yr survival rates are as high as 90-99% [25,31].Survival is favourable in children even in metastatic disease than adults, since pulmonary metastases can remain stable for extended periods [28,32].…”
Section: Clinical Features and Behaviourmentioning
confidence: 99%
“…Some surgeons cite the excellent survival in these patients counterbalancing the morbidity of aggressive surgery, and hence recommend conservative surgery [35,36] Most surgeons prefer to perform a total thyroidectomy for pediatric DTCs [6,7,22,25,29,[37][38][39][40], and the arguments in favour of this are multifold: (a) Multifocal disease occurs in 40% of pediatric PTC, and has a greater risk for recurrence; (b) Pediatric DTC commonly has regional lymph node disease and a greater risk for distant metastasis; (c) Total thyroidectomy will facilitate the future use of radioactive iodine (RAI) where indicated; (d) Postoperative RAI scans and thyroglobulin assays can be best used after total thyroidectomy, these are especially useful in picking pulmonary metastases that may be undetected on initial X-ray. We found that an initial X-ray of chest picked only about 31% of pulmonary metastases [3].…”
Section: Treatment -Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In a large retrospective study of pediatric patients with PTC who had extended follow-up, partial thyroidectomies carried larger rates of disease recurrence than bilateral thyroidectomies. 1 Further understanding of the genetics of pediatric PTC may help stratify patients and identify subgroups who could safely be treated with subtotal thyroidectomy. Tumor genetics of course can present opportunities for targeted therapy, which could be used as adjuvant therapy for individuals with very limited disease treated with subtotal thyroidectomy or in the rare, unfortunate patients with recalcitrant, advanced disease.…”
Section: Commentmentioning
confidence: 99%
“…2016;140:134-139; doi: 10.5858/ arpa.2014-0612-OA) P apillary thyroid carcinoma (PTC) is an uncommon tumor in the pediatric population. Despite having an excellent prognosis with long-term mortality rates of less than 1%, 1,2 pediatric patients with PTC tend to present with advanced disease often with increased rates of extrathyroidal tumor extension, lymphovascular invasion, and distant metastases. 1,[3][4][5] The distinct clinical nature of papillary thyroid cancer in the pediatric population has prompted interest in the molecular tumorigenesis.…”
mentioning
confidence: 99%